Vulneración del Derecho a la estabilidad laboral de los trabajadores del sector privado con contratos verbales en comparación con los contratos escritos, en el cantón Ibarra en el período 2022-2023 - Jiménez Guachán, Steven Joel (2024)
The right to job stability of workers is not expressly reflected within the Ecuadorian legal system, since in Art. 326 of the Constitution of the Republic of Ecuador, it is not mentioned\; However, it is a principle that has been established as a fundamental right, so the general objective is to analyze the violation of the right to job stability of workers belonging to the private sector in the Ibarra canton, specifically those subject to verbal contracts, establishing significant comparisons with their peers that have written contracts, during the period between May and December 2023. The methodology based on the qualitative approach had to be followed, with a level of descriptive depth and as scientific methods used the legal partner, the normativist, the deductive and analytical, becoming systematic procedures that, together with the documentary review and interviews as research techniques, were essential to determine that the violation of the right to job stability of workers belonging to the private sector in the Ibarra canton, specifically those under The modality of verbal contracts, during the period between May and December 2023, was reflected by the proliferation of verbal contracts as a simpler, less solemn contractual form, which allows the worker to obtain employment without undergoing a competition or bureaucratic selection processes, but in reality the disparities between both contracts, the verbal and the written, are palpable, which, in themselves, violate the right to job stability and continuity.